2023
DOI: 10.3389/fpsyg.2023.1301127
|View full text |Cite
|
Sign up to set email alerts
|

Can tourists become disciples? The formation and mechanism of place conversion in traditional Chinese villages

Luyao Xu,
Lei Shi,
Xin Wang
et al.

Abstract: Place attachment has been extensively studied in the field of tourism. However, it is important to recognize that place attachment alone may not fully capture the emotional expression of tourists’ spiritual beliefs and their sense of belonging to a destination. Therefore, a more comprehensive attachment theory is needed to encompass higher dimensions. This article focuses on the ancient Chinese villages of Yantou, Cangpo, and Furong from a tourist perspective, and introduces genius loci in architectural phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In studies on tourist place attachment, previous research results indicated that tourists' perceived value can positively influence place identity [53]. Xu's research suggested that through the place conversions, tourists developed a sense of belonging and appreciation for architectural art, and were thus given meaning and developed place identity with the village [54]. In this study, the level of neighborhood features and cultural preservation in personal evaluations are part of cultural value, while overall environmental evaluations are part of quality value, and residents' perceived value similarly positively influences place identity from these aspects.…”
Section: Factors Influencing Residents' Place Identity In Residential...mentioning
confidence: 99%
“…In studies on tourist place attachment, previous research results indicated that tourists' perceived value can positively influence place identity [53]. Xu's research suggested that through the place conversions, tourists developed a sense of belonging and appreciation for architectural art, and were thus given meaning and developed place identity with the village [54]. In this study, the level of neighborhood features and cultural preservation in personal evaluations are part of cultural value, while overall environmental evaluations are part of quality value, and residents' perceived value similarly positively influences place identity from these aspects.…”
Section: Factors Influencing Residents' Place Identity In Residential...mentioning
confidence: 99%